\(\dfrac{-6}{25}\)=??

Các bạn giúp mk vs nha

...">

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 6 2017

\(2,25:\dfrac{-6}{25}=\dfrac{9}{4}:\dfrac{-6}{25}\\ =-\dfrac{9}{4}\cdot\dfrac{25}{6}=-\dfrac{3}{4}\cdot\dfrac{25}{2}\\ =-\dfrac{75}{8}\)

26 tháng 6 2017

\(2.25:\dfrac{-6}{25}\) = \(\dfrac{9}{4}:\dfrac{-6}{25}=\dfrac{9}{4}.\dfrac{25}{-6}=\dfrac{3}{4}.\dfrac{25}{-2}=\dfrac{75}{-8}=\dfrac{-75}{8}\)

1 tháng 7 2017

a, Ta có

\(\dfrac{111}{37}< x< \dfrac{91}{37}\Leftrightarrow3< x< 7\Leftrightarrow x\in\left\{4,5,6\right\}\)

b,Ta co

\(\dfrac{-84}{14}< 3x< \dfrac{108}{9}\Leftrightarrow3.\dfrac{-28}{14}< 3x< 3.\dfrac{36}{9}\Leftrightarrow\dfrac{-28}{14}< x< \dfrac{36}{9}\Leftrightarrow-2< x< 4\Leftrightarrow x\in\left\{-1,0,1,2,3\right\}\)

3 tháng 7 2017

thank bạn

20 tháng 7 2017

\(\dfrac{3}{-2}=\dfrac{-9}{6};\dfrac{-1}{-7}=\dfrac{1}{7}\)

Sắp xếp:

\(\dfrac{-1}{-7};\dfrac{0}{8};\dfrac{-7}{6};\dfrac{3}{-2}\)

20 tháng 7 2017

thanks Mới vô

26 tháng 6 2017

\(\dfrac{-5}{11}+\left(\dfrac{-6}{11}+1\right)=\dfrac{-5}{11}+\dfrac{-6}{11}+1=-1+1=0\)

17 tháng 8 2018

a,\(\frac{25}{42}-\frac{20}{63}=\frac{5}{18}\)

b,\(\frac{9}{50}-\frac{13}{75}-\frac{1}{6}\)

=\(\frac{1}{150}-\frac{1}{6}\)

=\(-\frac{4}{25}\)

c,\(\frac{2}{15}+\frac{-2}{65}-\frac{4}{39}\)

=\(\frac{32}{195}-\frac{4}{39}\)

=\(\frac{4}{65}\)

17 tháng 8 2018

a,=75/126-40/126=35/126=5/18

b,=27/150-26/150-25/150=-4/25

c,=26/195+-6/195-20/195=0

2 tháng 2 2018

a) 7.28=x.x

=> 196=x2

=> \(\left(\pm14\right)^2=x^2\)

=> x=\(\pm14\)

b) DK: x≠-17

pt<=> 4.(10+2)=6.(17+x)

=> 4.12=17.6+6x

=> 48-102=6x

=>-66=6x

=>x=-11

c) 7.(x+40)=6.(17+x)

=> 7x+280=102+6x

=> 7x-6x=102-280

=> x=-178

2 tháng 2 2018

Giải:

a) \(\dfrac{7}{x}=\dfrac{x}{28}\)

\(\Leftrightarrow x^2=196\)

\(\Leftrightarrow x=\pm\sqrt{196}=\pm14\)

Vậy ...

b) \(\dfrac{10+2}{17+x}=\dfrac{3}{4}\)

\(\Leftrightarrow40+8=51+3x\)

\(\Leftrightarrow3x=40+8-51=-3\)

\(\Leftrightarrow x=-\dfrac{3}{3}=-1\)

Vậy ...

c) \(\dfrac{40+x}{17+x}=\dfrac{6}{7}\)

\(\Leftrightarrow280+7x=102+6x\)

\(\Leftrightarrow7x-6x=102-280\)

\(\Leftrightarrow x=-178\)

Vậy ...

4 tháng 10 2017

\(linh_1=\dfrac{1}{1.2.3}+\dfrac{1}{2.3.4}+\dfrac{1}{3.4.5}\)

\(linh_1=\dfrac{1}{2}\left(\dfrac{1}{1.2}-\dfrac{1}{2.3}+\dfrac{1}{2.3}-\dfrac{1}{3.4}+\dfrac{1}{3.4}-\dfrac{1}{4.5}\right)\)

\(linh_1=\dfrac{1}{2}\left(\dfrac{1}{1.2}-\dfrac{1}{4.5}\right)\)

\(linh_1=\dfrac{1}{2}\left(\dfrac{1}{2}-\dfrac{1}{20}\right)=\dfrac{1}{2}.\dfrac{9}{20}=\dfrac{9}{40}\)

\(linh_2=\dfrac{1}{1.2.3}+\dfrac{1}{2.3.4}+\dfrac{1}{3.4.5}+...+\dfrac{1}{8.9.10}\)

\(linh_2=\dfrac{1}{2}\left(\dfrac{1}{1.2}-\dfrac{1}{2.3}+\dfrac{1}{2.3}-\dfrac{1}{3.4}+\dfrac{1}{3.4}-\dfrac{1}{4.5}+...+\dfrac{1}{8.9}-\dfrac{1}{9.10}\right)\)\(linh_2=\dfrac{1}{2}\left(\dfrac{1}{1.2}-\dfrac{1}{9.10}\right)\)

\(linh_2=\dfrac{1}{2}\left(\dfrac{1}{2}-\dfrac{1}{90}\right)=\dfrac{1}{2}.\dfrac{22}{45}=\dfrac{11}{45}\)

4 tháng 10 2017

a/ \(G=\dfrac{1}{1.2.3}+\dfrac{1}{2.3.4}+\dfrac{1}{3.4.5}\)

\(\Leftrightarrow2G=\dfrac{2}{1.2.3}+\dfrac{2}{2.3.4}+\dfrac{2}{3.4.5}\)

\(\Leftrightarrow2G=\dfrac{1}{1.2}-\dfrac{1}{2.3}+\dfrac{1}{2.3}-\dfrac{1}{3.4}+\dfrac{1}{3.4}-\dfrac{1}{4.5}\)

\(\Leftrightarrow2G=\dfrac{1}{1.2}-\dfrac{1}{4.5}\)

\(\Leftrightarrow2G=\dfrac{1}{2}-\dfrac{1}{20}\)

\(\Leftrightarrow2G=\dfrac{9}{20}\)

\(\Leftrightarrow G=\dfrac{9}{40}\)

b/ \(H=\dfrac{1}{1.2.3}+\dfrac{1}{2.3.4}+.....+\dfrac{1}{8.9.10}\)

\(\Leftrightarrow2H=\dfrac{2}{1.2.3}+\dfrac{2}{3.4.5}+.....+\dfrac{2}{8.9.10}\)

\(\Leftrightarrow2H=\dfrac{1}{1.2}-\dfrac{1}{2.3}+\dfrac{1}{2.3}-\dfrac{1}{3.4}+.....+\dfrac{1}{8.9}-\dfrac{1}{9.10}\)

\(\Leftrightarrow2H=\dfrac{1}{1.2}-\dfrac{1}{9.10}\)

\(\Leftrightarrow2H=\dfrac{1}{2}-\dfrac{1}{90}\)

\(\Leftrightarrow2H=\dfrac{22}{45}\)

\(\Leftrightarrow H=\dfrac{22}{90}\)

22 tháng 9 2016

b1: a, 612.(15+19-34)=612.0=0

b,414.(37.4+23.4-240)=414.0=0

c,(517.125-518.25)+63:23=(517.53-518.52)+33=0+27=27

b2:a,143+7.(n-17)=206

===> 7.(n-17)=206-143=63

====>n-17=63:7=9

=====>n=9+17=26

vậy n=26

b,128-28:(15-n)=124

====>28:(15-n)=128-124=4

=====> 15-n=28:4=7

=====> n=15-7=8

vậy n=8

c,3n.2+48=210

====>3n.2=210-48=162

====>3n=162:2=81=34

====>n=4

vậy n=4